Genetic polymorphism of sterol transporters in children with future gallstones - Nissinen, Markku J.; Pitkänen, Niina; Simonen, Piia; Gylling, Helena; Viikari, Jorma; Raitakari, Olli; Lehtimäki, Terho; Juonala, Markus; Pakarinen, Mikko P. (Digestive and liver disease, 2018)
Gallstone disease is related to hypersecretion of cholesterol in bile, and low serum phytosterol levels. We examined how genetic polymorphisms of sterol transporters affect childhood cholesterol metabolism trait predicting adult gallstone disease. In retrospective controlled study, we determined D19H polymorphism of ABCG8 gene, genetic variation at Niemann-Pick C1-like 1 (NPC1L1) gene locus (rs41279633, rs17655652, rs2072183, rs217434 and rs2073548), and serum cholesterol, noncholesterol sterols and lipids in children affected by gallstones decades later (n = 66) and controls (n = 126). In childhood, phytosterols were lower (9.7%–23.4%) in carriers of risk allele 19H compared to 19D homozygotes. Lowest campesterol/cholesterol tertile consisted of 1.9-times more future gallstone subjects, and 3.7-times more 19H carriers than highest one. Campesterol/cholesterol-ratio was highest in 19D homozygote controls, but ∼11% lower in gallstone 19D homozygotes and ∼25% lower among gallstone and control carriers of 19H. Gallstone subjects with alleles CC of rs41279633 and TT of rs217434 of NPC1L1 had ∼18% lower campesterol/cholesterol-ratio compared to mutation carriers. Risk trait of cholesterol metabolism (low phytosterols) in childhood favouring cholesterol gallstone disease later in adulthood is influenced by risk variant 19H of ABCG8 and obviously also other factors. NPC1L1 variants have minor influence on noncholesterol sterols.